Strategy to Increase Sales at Caffetto as A Coffee Company - Jaya, Fandy Mahatma; Taufik, Tonton (The Indonesian Journal of Business Administration, 2015)
Abstract. As the fourth largest coffee producer of the world, the welfare of coffee farmers in Indonesia is still much below the average and less powerful. Then, the potency of Indonesian coffee itself is considered less than optimal because most of Indonesia’s coffee production is Robusta (80%) and Arabica (20%). Actually, the most circulation of coffee around the world (70%) is dominating with Arabica, and then Robust (29%), and 1% is other species. And also Indonesia coffee sales has been primarily as raw materials commodity without processing, so it will be just raw materials commodity without value-added.The anxiety of this condition led to an idea to set up a coffee company that can process and produce high quality coffee, able to empower all involved stakeholder (especially coffee farmers). Caffétto as a coffee processing company has a core competence in the field of premium Arabica roasted coffee beans. Caffétto has high commitment to produce high quality and value product. Not only premium Arabica roasted coffee beans (whole beans) production, but more than that, Caffétto also provide some services such as coffee roasting service, coffee consultancy, and catering. As a start-up company, Caffeto still faces many problems. To solve those problems, this research tries to find out the root cause of all problems in Caffétto business and formulate solutions to Caffétto can grow and achieve sustainable competitive advantage. From the survey and analysis of problems, it can be concluded that the root cause found in this research are: (1) Wrong market segment. Caffétto only assume that their market segment is all cafes regardless of whether the cafe already had a roasting machine or not, (2) Promotion is not optimal and human resources have not been sufficient in the field of marketing, customer service, and operating, (3) The brand awareness is still low.To overcome these problems, Caffetto make some changes in some aspects by applying differentiation-focus strategy. Caffétto need to implement the specific strategies in several aspects, such as marketing, HR, financial strategy, and branding strategy. In marketing strategy, Caffétto can run some promotions tools of IMC that advertise their products and services in social media, magazines and participating in exhibitions. Those strategies are scheduling for 12 months, beginning November 2014 until October 2015. Keyword: Coffee, SME, brand awareness, increase sales, Integrated Marketing